X-ray fluorescence and multiband imaging of medieval children's shoes - Bottura Scardina, Silvia; Hacke, Marei; Norrehed, Sara (Swedish National Heritage Board, 2026)
Examination of two medieval children’s shoes from the collections of the National Historical Museums: 580563_HST and 595827_HST. XRF mapping and Multiband imaging (VIS, IRR, UVL) was performed for documentation and to visualize traces of paint materials to improve our understanding of the shoes’ original appearance.
Keywords: multiband imaging; heritage science; Östra Aros; Uppsala; Archaeology; Shoes; Leather; History, Medieval; XRF; RAÄ-2025-3042; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi